Assessment of Chicken-Egg Membrane as a Dressing for Wound Healing. (March 2016) - Guarderas, Fernando; Leavell, Yaowaree; Sengupta, Trisha; Zhukova, Mariya; Megraw, Timothy L.
ABSTRACT: OBJECTIVES: To examine the efficacy of the folk remedy of chicken-egg membrane dressing on wound healing. DESIGN: Full-thickness excisional wounds were created on 14 male Sprague-Dawley rats in 2 separate trials. Each animal received 2 wounds on the upper back. One wound was untreated, and the other was dressed with chicken-egg membrane to assess its impact on wound healing. Half of the rats received egg membrane treatment on the inferior wound, whereas the other half received egg membrane treatment on the superior wound. Membrane replacement, wound debridement, and imaging were done on days 5, 8, and 10 and then imaging continued on days 12, 14, 16, 18, and 20 of the experiment. Healing rate was measured based on the wound area over the 20 days of the experiment. RESULTS: The wounds dressed with chicken-egg membrane had a significantly ( P < .01) faster rate of healing compared with the control at the early stages of healing between days 0 and 5. This group healed 21% faster during this early phase, compared with the control group. Overall, however, wound healing rates were indistinguishable from days 5 to 20. CONCLUSION: Chicken-egg membrane dressing significantly improves healing of cutaneous wounds in the early stages of wound healing.